An enigmatic clinical presentation of plasma cell granuloma of the oral cavity - Pravesh Kumar Jhingta; Kavita Mardi; Deepak Sharma; Vinay Kumar Bhardwaj; Ashu Bhardwaj; Nitin Saroch; Nishant Negi (Wolters Kluwer Medknow Publications, 2018)
Plasma cell granuloma is a rare benign lesion characterized by the infiltration of plasma cells; primarily occurring in the lungs. It is also seen to occur in the brain, kidney stomach, heart, and so on but its intraoral occurrence is a rarity. This case report represents one of the uncommon locations in the oral cavity affected by plasma cell granuloma, its clinical and histological features, and establishes the differential diagnosis with other malignant or benign disease entities and planning the treatment accordingly. This report discusses the diagnostic enigma and the associated terminology of plasma cell granulomas and reinforces the need for performing biopsy and a histopathological or immune histochemical study, irrespective of the clinical features and clinical diagnosis of the lesion. In this case a 52-year-old female, presented with gingival enlargement in the mandibular anterior region, treated by excisional biopsy. Histological evaluation revealed plasma cell infiltrates in the connective tissue. The immune-histochemistry revealed kappa and lambda light chains with a polyclonal staining pattern, which confirmed the diagnosis of plasma cell granuloma.